A porção sul do Grupo Vazante entre Lagamar e Coromandel (MG): estratigrafia, geocronologia e fosfogênese neoproterozoica - Carla Sofia de Sousa Marques (2019)
The Vazante Group (northwest of Minas Gerais) represents a pelitic-carbonate succession deposited during the Meso-Neopreoterozoic between the Brasília Belt and the São Francisco Craton. In its southern portion, between Lagamar and Coromandel towns, the collisional phase of the Brasília Belt was responsible for stratigraphic inversion, placing the older meso-neoproterozoic Lagamar-Serra do Garrote formations over the younger neoproterozoic Santo Antônio do Bonito-Rocinha formations. The Lagamar Formation presents carbonate facies related to a reef environment: fore reef (carbonate reworking along a slope), reef (stromatolytic structures in isolated reefs) and back reef (shallow environment with high salinity protected by the reef barrier). Normalizing by PAAS, the REE data from the collected samples do not follow the typical pattern of marine carbonates, showing LREE/HREE ≈ 1.0, positive La anomaly, absence of Ce and Gd anomalies and low Y/Ho ratios at 29-39. The isotopic data showed δ13C values ranging from -0.14 and 2.20‰, and δ18O from -9.82 to -3.18‰ showing homogeneity of values and primary signature of 87Sr/86Sr around 0.7068. The basal units of the Vazante Group, the Santo Antônio do Bonito and Rocinha formations, present different stratigraphic records and younger ages than the remaining of the Vazante Group. These units are characterized by diamictites, sandstones, pelites and rare carbonates originated from a subaqueous gravitational sedimentation, composing a slope-apron system. U-Pb geochronological data from detrital zircon grains indicate a neoproterozoic maximum depositional age for both formations (934 ± 8 Ma) and main source of zircons from Paleoproterozoic (mainly Rhyacian and Orosirian) to Mesoproterozoic (Calymmian and Ectasian), whose provenances are from the São Francisco Paleocontinent. This sedimentation is correlated to the glaciogenic Jequitaí Formation (Bambuí Group). From east to west, the glacial sediments were reworked by gravitational processes, moving to a slope-apron system on the margin of the São Francisco Paleocontinent. The Sm-Nd data also confirm this similarity, especially between the Santo Antônio do Bonito Formation and Jequitaí formations, with paleoproterozoic model ages (TDM = 1.8 to 2.1 Ga). Due to the complete absence of ice-rafted debris within fine-grained sediments in the Santo Antônio do Bonito Formation, the gravitational reworking was the main process of diamictites deposition, probably during a period of ice retreat and sea level rise (syn to post-glacial stage). The Rocinha Formation presents more fine-grained lithotypes, increase of neoproterozoic zircons and younger TDM ages, indicating sedimentation during a post-glacial stage and with a significant provenance change. Sedimentary phosphate deposits from the Vazante Group are described and compared. The Coromandel deposit (basal), as well as Rocinha and Lagamar (top), are related to a large phosphogenetic postglacial transgressive event. The phosphate enrichment occurs in rhythms (phosphoarenites rich in fine/medium intraclasts, fluorapatites and cryptocrystaline matrix), later enriched by supergenic processes, forming wavellite in fractures.